WHY ARE LOCAL AND TRADITIONAL FOOD PRODUCERS NECESSARY IN ROMANIAN RETAIL? - Brindusa Mariana BEJAN; Ciprian Marcel POP; Gabriela Nicoleta SIRBU; Iulia Diana ARION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article analyzes the impact that local and traditional producers have on retail in Romania. The analysis we conducted reflects the presence of a relatively small number of producers in the Romanian market, being divided only into certain product categories, mainly food items. Therefore, to become known, the most important option available to them is to collaborate with major retailers in the market. Of course, the limited number of producers restricts the selection options for customers. From a methodological perspective, to complete this article, we conducted documentary research on the number of existing producers and their segmentation and qualitative research. Thus, we interviewed people working with the retailer with the largest number of employees in the Romanian market to find out the number of producers they collaborate with and the criteria these producers must meet to be selected. Additionally, for the analysis part, we examined the most important digital platform that promotes local producers, aiming to connect the rural and urban environments.